META-ANALYSIS OF PROBLEM BASED LEARNING MODELS ON PHYSICS PROBLEM SOLVING ABILITIES - Putri, Fhadira Insani; Deswalman, Deswalman; Tosin, Adelakun Isaac (EduFisika: Jurnal Pendidikan Fisika, 2024)
The ability to solve these problems can be built and improved through the use of the Problem Based-Learning (PBL) learning model. This research aims to analyze the effect of using the Problem Based Learning model on students' Physics problem solving abilities. The method used in this research is meta-analysis. Meta-analysis is carried out by summarizing previously existing research data. Data collection was carried out by reviewing and searching ten online articles that examined the influence of the Problem Based Learning Model on physics problem solving abilities. The population in this study is research articles about the PBL model published online in the period 2018-2023. The samples taken were ten journals related to the research title. In this research, to find the right articles, search keywords were use, namely Problem Based Learning, the ability to solve problems on websites or online article pages. The criteria for articles taken as reference material in this meta-analysis are to contain at least the average pretest score before using the PBL model and the posttest score after using the PBL model to make it easier to determine the effect size. The results of the meta analysis carried out show that there is an influence of learning using the Problem Based Learning model on increasing students' Physics problem solving abilities.